Environmental policy an economic perspective - Walker, Thomas (Thomas J.).; Sprung-Much, Northrop 1991-; Goubran, Sherif 1991- (Hoboken, NJ Wiley-Blackwell, 2020)
"Global environmental challenges have caused a range of policy solutions, approaches, and models to emerge. As these challenges are expected to intensify in the near future, environmental policy and its instruments are increasingly becoming a topic of discussion, action, and disagreement in academic, professional, and mass media outlets. This fixation on the topic of policy is well-justified considering the consequences policy can have on all levels of society - global, national, sectoral, organizational, and even personal. Policy has a vital role in reducing environmental damage, incentivizing positive environmental behavior, and guiding practice toward a more sustainable future. While most policies have economic repercussions, environmental policies, and specifically new environmental policy instruments, have exhibited a special and complex relation to the economy. The environment can thus be considered an envelope encompassing and sustaining the economic system - much more than just a factor of production"--
An introduction to the current landscape : environmental policy and the economy / Tyler Schwartz and Sherif Goubran -- Responses to climate change worldwide : individual preferences and policy actions around the world / Andrew Brennan, Astghik Mavisakalyan, and Yashar Taverdi -- Legislation or economic instruments for a successful environmental policy? : reflections after "Dieselgate" / Theodoros Zachariadis -- Environmental legislation and small-and-medium-sSized enterprises (SMEs) : a literature review / Eleni Sfakianaki -- Bulk water pricing policies and strategies for sustainable water management : the case of Ontario, Canada / Micheal Wood, Horatiu Rus, Olaf Weber, and Guneet Sandhu -- The role of water pricing policies in steering urban development : the case of the Bogota region / Camilo RomeroChapter -- Effective environmental protection and regulatory quality: a national case study of China / Sharanya Basu Roy -- The EU legal and regulatory framework for measuring damage risks to the biodiversity of the marine environment / Ivelin Zvezdov -- Redefining nature and wilderness through private wildlife ranching : an economic perspective of environmental policy in South(ern) Africa / Tariro Kamuti -- Climate change regulations and accounting practices : optimization for emission-intensive publicly traded firms / David Lont and Carol Pompare -- The economic aspects of the adoption of renewable energy policies in developing countries : an overview of the Brazilian wind power sector / Elia Alves and Andrea Steiner -- Ontario's energy transition : a successful case of a green jobs strategy? / Bruno Arcand -- Ethical and sustainable investing and the need for carbon-neutrality / Quintin Rayer -- Building sustainable communities through market based instruments / Ying Zhou, Amelia Clarke, and Stephanie Cairns -- Climate justice in food security : experience from climate finance in Bangladesh / Muhammad Abdur Rahaman and Mohammad Mahbubur Rahman -- A survey of UK-based ethical and sustainable fund managers' investment processes addressing plastics in the environment / Quintin Rayer.
Includes bibliographical references and index.
Keywords: Environmental policy -- Economic aspects; Global environmental change -- Economic aspects; Climatic changes -- Economic aspects; Sustainable development -- Economic aspects; Renewable energy resources -- Economic aspects